2015
DOI: 10.1186/s12867-015-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of Sertoli cells with androgen receptor alters gene expression without androgen stimulation

Abstract: BackgroundAndrogens play an important role for the development of male fertility and gained interest as growth and survival factors for certain types of cancer. Androgens act via the androgen receptor (AR/Ar), which is involved in various cell biological processes such as sex differentiation. To study the functional mechanisms of androgen action, cell culture systems and AR-transfected cell lines are needed. Transfection of AR into cell lines and subsequent gene expression analysis after androgen treatment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Although recent microarray studies have identified similar numbers of up-regulated and down-regulated genes in Sertoli cells during the process of postnatal maturation [76], and especially in response to androgens in Sertoli cells [6,77,78], most of the androgen-regulated genes thoroughly studied so far are positively regulated by androgens. Amongst those, Rhox5 (reproductive homeobox-5), formerly known as Pem , is perhaps one of the best characterized androgen-responsive genes [79].…”
Section: Ar Signaling In Sertoli Cellsmentioning
confidence: 99%
“…Although recent microarray studies have identified similar numbers of up-regulated and down-regulated genes in Sertoli cells during the process of postnatal maturation [76], and especially in response to androgens in Sertoli cells [6,77,78], most of the androgen-regulated genes thoroughly studied so far are positively regulated by androgens. Amongst those, Rhox5 (reproductive homeobox-5), formerly known as Pem , is perhaps one of the best characterized androgen-responsive genes [79].…”
Section: Ar Signaling In Sertoli Cellsmentioning
confidence: 99%
“…The stable transduction of AR into WPMY human prostate myofibroblasts significantly altered their gene expression pattern compared to those transduced with empty vector, in the absence of DHT [ 27 ]. Knockdown of AR by siRNA in an AR-positive cancer-associated fibroblast line produced significant differences in the expression of several growth factor genes, and the proliferation and migration of PC3 cells in transwell co-cultures [ 40 ], and the transfection of human AR into AR-deficient mouse Sertoli cells significantly altered the expression of 672 genes in the absence of androgen stimulation [ 41 ]. These latter two studies did not specify whether stripped medium was used.…”
Section: Discussionmentioning
confidence: 99%